2017
DOI: 10.7287/peerj.preprints.2464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential connectivity among American lobster fisheries as a result of larval drift across the species’ range in eastern North America

Abstract: We used a bio-physical model to estimate for the first time the effect of larval drift on potential connectivity among American lobster (Homarus americanus) fisheries management areas over the geographic range of the species. The model predicted drift of larvae over distances of 50-805 km (mean = 129 km), which connected many management areas and caused marked spatial heterogeneity in retention and self-seeding versus export and import of larvae by different fisheries areas. Including mortality functions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 43 publications
(129 reference statements)
1
26
0
Order By: Relevance
“…Lobster recruitment since 2013 in these areas has remained low compared to its pre-2013 values and appears to have been even lower than in 2013 in the year 2016 ( Wahle & Carloni, 2017 ). Potential settlement of lobster larvae in the Gulf of Maine-Bay of Fundy system and the Scotian Shelf has also been predicted by a bio-physical dispersal model of the species’ range ( Quinn, Chassé & Rochette, 2017 ) to have been extremely low in 2013 (BK Quinn, J Chassé, and R Rochette, pers. comm., 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lobster recruitment since 2013 in these areas has remained low compared to its pre-2013 values and appears to have been even lower than in 2013 in the year 2016 ( Wahle & Carloni, 2017 ). Potential settlement of lobster larvae in the Gulf of Maine-Bay of Fundy system and the Scotian Shelf has also been predicted by a bio-physical dispersal model of the species’ range ( Quinn, Chassé & Rochette, 2017 ) to have been extremely low in 2013 (BK Quinn, J Chassé, and R Rochette, pers. comm., 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Values of the NAO index for each month were obtained from the Hurrell et al (2003) database ( National Center for Atmospheric Research Staff, 2018 ). Oceanic circulation effects were assessed by extracting potential total annual settlement (= total summer settlement) in the Minas Basin predicted by a bio-physical oceanographic model of larval dispersal, originally developed for American lobster ( Quinn, Chassé & Rochette, 2017 ) but with development times of larvae modified for eastern North American green crabs (after Dawirs, 1985 ). Both potential settlement in the previous and same year as density sampling were considered as potential predictors of crab abundance.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most accessible approaches to making such estimates is the use of physical oceanographic models coupled to biophysical computer models of larval dispersal (Caputi et al, 2018; Siegel et al, 2003; Silva et al, 2019). Such approaches have been used previously for the American lobster across its range (Chassé & Miller, 2010; Gendron et al, 2019; Harding et al, 2005; Incze et al, 2010; Katz et al, 1994; Quinn et al, 2017; Xue et al, 2008). These modeling studies indicated that larval dispersal potentially connects lobster subpopulations and fisheries in different locations and regions, although much uncertainty still remains concerning the quality and implications of their predictions.…”
Section: Introductionmentioning
confidence: 99%
“…These modeling studies indicated that larval dispersal potentially connects lobster subpopulations and fisheries in different locations and regions, although much uncertainty still remains concerning the quality and implications of their predictions. For example, incomplete information concerning various aspects of larval biology, including behavior, mortality, and development (Caputi et al, 2018; Gendron et al, 2019; Quinn, 2014a; Quinn et al, 2017), has been included in these models, with potentially important, but unquantified, impacts on model predictions and their realism. Ultimately, estimates of “realized connectivity” accounting for the effects of mortality and all other relevant biological and physical factors are needed to support management of lobster fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…Warmer than usual conditions in surface waters are also likely to accelerate larval development (Ouellet & Sainte‐Marie, ; Yamamoto et al, ) and possibly reduce the extent of larval drift and supply to some areas (e.g. Quinn, Chassé, & Rochette, ).…”
Section: Introductionmentioning
confidence: 99%